2021
DOI: 10.1155/2021/9501648
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Ticks Infesting Dairy Cattle and the Pathogens They Harbour in Smallholder Farms in Peri-Urban Areas of Nairobi, Kenya

Abstract: This study aimed at determining the tick species infesting dairy cattle in Nairobi, Kenya, and the pathogens they harbour. While ticks are well-known vectors of major bacterial pathogens of both veterinary importance and public health importance, few studies have investigated the range of the tick species and the associated pathogens, especially present in unique dairy production systems, which compromise animal welfare, such as those in peri-urban areas. A cross-sectional study was undertaken involving 314 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
2
2
0
Order By: Relevance
“…Rhipicephalus ( Boophilus ) (47.53%) was the most abundant tick genus in Ethiopia. This finding is in agreement with the report of the study done by ( Peter et al, 2021 ) in Kenya, where Rhipicephalus was the most abundant genera with a prevalence of 67.0%. Hyalomma was the least abundant tick species in Ethiopia, with a prevalence of 6.37%.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Rhipicephalus ( Boophilus ) (47.53%) was the most abundant tick genus in Ethiopia. This finding is in agreement with the report of the study done by ( Peter et al, 2021 ) in Kenya, where Rhipicephalus was the most abundant genera with a prevalence of 67.0%. Hyalomma was the least abundant tick species in Ethiopia, with a prevalence of 6.37%.…”
Section: Discussionsupporting
confidence: 93%
“…Hyalomma was the least abundant tick species in Ethiopia, with a prevalence of 6.37%. This report coincides with the previous studies with a prevalence of 4.7% and 13.8% by ( Teshome et al, 2016 ) and ( Peter et al, 2021 ) in Oromia, Ethiopia, and Nairobi, Kenya, respectively. However, the current study disagrees with the study reported by ( Fesseha and Mathewos, 2020 ) in Hossana district, Hadiya zone, Ethiopia, which stated that Hyalomma was the most abundant tick genus with a prevalence of 11.9%.…”
Section: Discussionsupporting
confidence: 93%
“…These trends facilitate interactions between livestock, humans, and wildlife in a complex environment, increasing the opportunity for pathogen spill-over events (Okal et al, 2020). Several tick-borne bacterial, viral, and parasitic agents have been documented in Kenya, including agents of anaplasmosis, ehrlichiosis, rickettsiosis, Crimean-Congo hemorrhagic fever (CCHF), babesiosis, and theileriosis (Omondi et al, 2017;Morrison et al, 2020;Okal et al, 2020;Chiuya et al, 2021;Getange et al, 2021;Peter et al, 2021), with occasional reporting of novel pathogens (Mwamuye et al, 2017). However, reports from wildlife are relatively rare and often focus on well-documented bacterial agents.…”
Section: Introductionmentioning
confidence: 99%
“…These include [39] [48] [49]. However, other authors have given prevalence ranging from 1.8% to 13.8% [45] [50] [51].…”
Section: Hyalomma Marginatummentioning
confidence: 99%